2005
DOI: 10.1108/09544780510627615
|View full text |Cite
|
Sign up to set email alerts
|

Graph theory and matrix approach for performance evaluation of TQM in Indian industries

Abstract: PurposeOnce the decision is taken to implement total quality management (TQM) in any organization, achieving TQM is a journey. It takes significant effort over an extended period of time. Seeks to propose a TQM performance index.Design/methodology/approachAn industry TQM performance index evaluates and ranks the various industries practicing TQM for a given period of time. Uses graph theory and a matrix approach.FindingsThe index is obtained from industry performance function, which is useful for identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…From literature it has been found that Wani and Gandhi (1999) have used data from previous research for selecting the values of the variables while Kulkarni (2005) used a questionnaire to measure each attribute in quantitative terms.…”
Section: Permanent Representation Of Gtpp System Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…From literature it has been found that Wani and Gandhi (1999) have used data from previous research for selecting the values of the variables while Kulkarni (2005) used a questionnaire to measure each attribute in quantitative terms.…”
Section: Permanent Representation Of Gtpp System Matrixmentioning
confidence: 99%
“…The permanent function is a mathematical model that helps determine index that can be used for comparison. GTA is a systematic and logical approach that is applied in various disciplines (Jurkat and Ryser 1966;Deo 2000;Attri et al 2014;Faisal et al 2007;Wani and Gandhi 1999;Kulkarni 2005;Dev et al 2014c). …”
Section: Graph Theoretic Approach (Gta)mentioning
confidence: 99%
“…Note that, during this process, the permanent function, and neither the determinant function nor the permutation function (which totally differs in its meaning), is used to provide the complete information of the assessed alternative without any loss (see [51]). Some recent studies have successfully resolved the selection decisions or alternative ranking problems using this method [54][55][56][57][58]. Within the scope of GTMA, in addition to the abovementioned articles, there have been studies using the AHP-GTMA hybrid approach [59][60][61].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digraph and matrix approach has been used extensively by a number of researchers in various engineering applications such as failure cause analysis [11], reliability evaluation [12], proactive fault identification [13], TQM evaluation [14,15], risk mitigation [16] and in other areas also. Digraph and matrix approach is a well systematic one which considers all the influencing factors (attributes) and its relative importance of one factor on the other on the objective.…”
Section: Interviewing Users To Identify Users' Needsmentioning
confidence: 99%